MEDICAL ERROR – GENERAL TERM AND ITS OVERVIEW IN RADIOLOGY - Opancina, Valentina D; Vojinovic, Radisa (Medicinski časopis, 2018)
Mistakes in the treatment of the diseased are part of everyday life. Both the knowledge of state law and appropriateness criteria can help the doctor to prevent complications in treatment and thus any legal issues with patients. The term professional error is traditionally associated with the physicians’ practices, and the term "medical error" has established, although it can be related to the actions of any healthcare professional. Radiology occupies an important place in the world of medicine due to its significance in the fields of diagnostics and treatment. Data on professional errors in the field of radiology have been searched in the judicial practice of the Republic of Serbia, which showed no final verdict against radiologists. An extensive search of publications in the field of law and medicine was conducted, which showed that there are no published papers with this topic in the Republic of Serbia, neither review nor original study. Therefore, the aim of this paper was to review the foreign literature, regardless of the type of legal system, in order to gain insight into this issue and prepare area for research in this field. It is important to note that there has been a significant increase in the number of court proceedings due to the medical error in radiology, which can be decreased by educating radiologists, radiology technicians and patients. This is an area that will experience expansion in the upcoming years and it is therefore important to implement timely education and to prevent mistakes that can be fatal to the patient.